STRUKTUR DAN KOMPOSISI HUTAN BEKAS PERLADANGAN DI DESA HILIFALAGO KECAMATAN ONOLALU KABUPATEN NIAS SELATAN - Bago, Adam Smith; Hulu, Versi Putra (Jurnal Sapta Agrica, 2022)
Forests can experience a decline as a result of various activities carried out by humans, one of which is shifting cultivation. Decreasing forest quality reduces plant carbon absorption and storage, thereby affecting plant biological activity and impacting biodiversity. This study aims (1) to understand the structure and of ex-swidden forest in Hilifalago village, Onolalu district, South Nias Regency, (2) to understand the composition of ex-swidden forest. This study uses a descriptive quantitative approach. This study used the plot method with a size of 40 x 40 m, the sampling technique was purposive sampling. Based on the results of the study, it was found that the structure of ex-swidden forest in Hilifalago Village, Onolalu District consisted of upper and lower canopy layers, namely stratum A, B, C, and D and the most commonly found was the canopy layer in stratum C, while the composition of ex-swidden forest in the district Onolalu consists of 8 families and 10 species with 44 individuals. The highest important value index was found in Hevea brasiliensis Muell. Arg. (110.68%) and the family that was classified as the dominant family was the Euphorbiaceae